The effect of dissolved oxygen on the oxidation of an austenitic steel in supercritical water. (4th March 2022) - Yang, Xu; Xu, Guangmin; Che, Chang; Zhu, Zhongliang; Chen, Xinzhong; Qian, Linfeng; Qian, Gong; Zhang, Naiqiang
ABSTRACT: The oxidation experiments of austenitic steel TP347HFG were carried out at 620°C under 25 MPa in supercritical water with the dissolved oxygen content of 0–2000 ppb. The oxidation rate of TP347HFG increased with the rise in dissolved oxygen content. A double-layered oxide scale composed of a Fe-rich outer layer and a Cr-rich inner layer developed on the TP347HFG steel surface. Haematite was detected in supercritical water with 2000 ppb dissolved oxygen while absent in deaerated supercritical water. The content of dissolved oxygen has a great impact on the formation and distribution of Cr2 O3 . A thicker and continuous Cr2 O3 were observed in the grain boundary near the interface of oxide and the substrate in deaerated supercritical water. The Cr evaporation may be responsible for the oxidation resistance of TP347HFG steel in supercritical water with different dissolved oxygen content. The influence mechanisms of dissolved oxygen on oxidation rate and oxides composition were discussed in this paper.